Category Based Search for Collaborative Environment - Salokhe, TV; Pawar, PM (International Journal of Computer Sciences and Engineering, 2025)
The Foremost goal of CBSCE (Category based search for Collaborative Environment) is to minimize the time required to obtain particular information, also increase user satisfaction with the result that they are going to get for the specific search. CBSCE provides enhanced search results based on previous user interplays with the systems by tracking each user's performance every time user logs in the system. Existing system used HMM(Hidden markow Model) model which is intensely complicated and hard to extend further, as the primary goal is session clustering, session clustering along with HMM model is what very hard to link such results which take time and less efficient operation. It provides user interaction related search based on existing interactions, for that HMM, is used, Instead of HMM SVM(Support Vector Machine) is a technique you can customize as per the need and which is very flexible with session clustering.